Do athletes benefit from preoperative physical therapy before ACL-reconstruction? - Gränicher, P.; Scherr, J. (Sport-Orthopädie - Sport-Traumatologie, 2021)
Successful return to sport (RTS) and competition (RTC) rates are important factors when evaluating the successfulness of anterior cruciate ligament reconstruction (ACLR). Although functional outcomes are mostly satisfying after rehabilitation, a great proportion of athletes does not return to their preoperative level of performance. Low preoperative leg symmetry index in the strength development of quadriceps and hamstring muscles, female sex, older age, fear of reinjury, low self-efficacy and long waiting times without any intervention between injury and surgery can predict lower RTS rate after ACLR. Preoperative physical therapy addressing potential risk factors may improve RTS in elite and amateur athletes. Although athletes usually show high functional performance after injury, prehabilitation may - nevertheless - enhance successful RTC. Identifying risk factors for not RTS after ACLR can contribute to the decision on modality of prehabilitation and timing for surgery. The development of evidence-based guidelines considering preoperative patient- and knee function-related state could provide additional information regarding necessity for prehabilitation.